Preparação de nanofio via deposição eletroquímica utilizando modelo de membrana porosa - Recco, Lucas Custodio [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
From the last decade of the twentieth century, the rapid growth of nanotechnology has resulted in the discovery of a number of forms of nanoparticles and nanoclusters. We can cite as an example: nanotubes, nanowires, nanobelts, and nanoconesnanoclusters which have a wide range of applications, particularly as catalysts magnetic material nanodevices, chemical sensors, degradation of toxic chemicals, or even as possible carriers for the isotope medical applications.. The first step is the production and characterization of nanowires multithreaded using different types of metals (nickel, silver, gold) and polymers (pyrrole), which are prepared by electrochemical deposition process. Will be held by the characterization of the same images of scanning electron microscopy (SEM) and transmission electron microscopy (TEM)

A partir da última década do século XX, o crescimento acelerado da nanotecnologia resultou na descoberta de uma série de formas de nanopartículasenanoagregados. Podemos citar como exemplo: nanotubos, nanofios, nanofitas, nanoclusters enanoconesque têm uma vasta gama de aplicações, em particular, como catalisadores, material magnético, nanodispositivos, sensores químicos, degradação de produtos químicos tóxicos, ou mesmo como possíveis portadores de isótopos para aplicações médicas. A primeira etapa consistirá na produção e caracterização de nanofiosmultisegmentados utilizando diferentes tipos de metais (níquel, prata, ouro) e polímeros (pirrol), os quais serão preparados pelo processo de deposição eletroquímica. Será realizada a caracterização dos mesmos por imagens de microscopia eletrônica de varredura (MEV) e por microscopia de transmissão eletrônica (TEM)
Keywords: Nanotecnologia; Nanoestrutura; Nanopartículas; Nanotechnology